2017
DOI: 10.5194/acp-17-15137-2017
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent rate coefficients for the reactions of the hydroxyl radical with the atmospheric biogenics isoprene, alpha-pinene and delta-3-carene

Abstract: Abstract. Pulsed laser methods for OH generation and detection were used to study atmospheric degradation reactions for three important biogenic gases: OH + isoprene (Reaction R1), OH +α-pinene (Reaction R2) and OH + -3-carene (Reaction R3). Gas-phase rate coefficients were characterized by non-Arrhenius kinetics for all three reactions. For (R1), k 1 (241-356 K) = (1.93 ± 0.08) × 10 −11 exp{(466 ± 12)/T } cm 3 molecule −1 s −1 was determined, with a room temperature value of k 1 (297 K) = (9.3± 0.4) × 10 −11 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Given the good agreement in the temperature dependence of k1 with other measurements, the simplest explanation is some systematic error in determining isoprene concentrations in the reaction cell. That explanation is supported by the recent studies of Dillon et al 22 who determined UV absorption cross sections for isoprene which are approximately 10% greater than those of Campuzano-Jost et al and in good agreement with another determination by Martins et al 111 Dillon et al re-evaluated the Campuzano-Jost data using their new cross sections, generally bringing the Campuzano-Jost et al data in closer agreement to the IUPAC evaluation.…”
Section: Master Equation Modelling and Comparison With Literaturementioning
confidence: 57%
See 1 more Smart Citation
“…Given the good agreement in the temperature dependence of k1 with other measurements, the simplest explanation is some systematic error in determining isoprene concentrations in the reaction cell. That explanation is supported by the recent studies of Dillon et al 22 who determined UV absorption cross sections for isoprene which are approximately 10% greater than those of Campuzano-Jost et al and in good agreement with another determination by Martins et al 111 Dillon et al re-evaluated the Campuzano-Jost data using their new cross sections, generally bringing the Campuzano-Jost et al data in closer agreement to the IUPAC evaluation.…”
Section: Master Equation Modelling and Comparison With Literaturementioning
confidence: 57%
“…Reaction R1 appears to be at its high pressure limit above 50 -100 Torr at room temperature, however, there is some controversy as to the onset of the pressure independent region. [19][20][21][22] There is no evidence of any significant role for the abstraction reaction at room temperature.…”
Section: C5h7 + H2o (R1b)mentioning
confidence: 98%
“…theoretically derived literature values. Dillon et al (2017) determined a temperature-dependent rate coefficient, for comparability with data in this work, only the rate coefficient determined at 304 K is used. Dillon et al (2017) determined a reaction rate constant of (8.1 ± 0.1) × 10 −11 cm 3 s −1 using an absolute rate approach and Atkinson et al (1986) reported a value of (8.7 ± 0.4) × 10 −11 cm 3 s −1 at 294 K using a relative rate determination approach.…”
Section: Rate Constant Of the Oh + ∆ 3 -Carene Reactionmentioning
confidence: 99%
“…The isoprene UV-Vis cross section is shown in (Figure 7). The data has been taken from (Dillon et al 2017) and is used for calculating the UV photolysis rate (see Section 3.3). The isoprene UV-Vis absorption peaks at 218 nm with σpeak = 7.93 ± 0.02 × 10 -17 cm -2 molecule -1 and covers a wavelength range of 118 nm to 278 nm.…”
Section: Uv-vis Cross Sectionmentioning
confidence: 99%
“…Figure 7. Isoprene UV-Vis absorption cross section taken from(Dillon et al 2017). The axes shows absorption cross section [cm 2 molecule -1 ] vs. wavelength[μm].…”
mentioning
confidence: 99%